On the Design of MAC Protocols for Low-Latency Hard Real-Time Discrete Control Applications Over 802.15.4 Hardware - Chintalapudi, Krishna; Venkatraman, Lakshmi (SPOTS-IPSN, 2008)
Discrete event control loops in modern-day machines often comprise a large number of sensors (50-200) reporting to a controller. Many discrete control applications must cater to hard real-time requirements i.e., sensors must communicate the occurrence of critical events to the controller within a real-time deadline (usually 5-50ms) specified by the control system’s design requirements. Messages reached after this deadline are considered lost. In the event of traffic bursts where several sensors may attempt to communicate with the PLC at the same time, messages from all the sensors must reach within the specified deadline. The metric for performance in such systems is then the probability that a message from all the sensors succeeds in being received at the controller within this deadline. Further, for such solutions to be viable, the sensors must last for several years without requiring change of batteries. In this paper we examine the potential for using 802.15.4 based radios for wireless sensing in low-latency hard real-time discrete event control applications.